The Rise of Behavioral Economics: A Quantitative Assessment. Issue 3 (25th July 2017) - Geiger, Niels
Abstract : This article is devoted to the issue of operationalizing and empirically measuring the development of behavioral economics, focusing on trends in the academic literature. The main research goal is to provide a quantitative, bibliometric assessment to answer the question of whether the relative importance of behavioral economics has increased over the past decades. After an introduction and a short summary of the history of behavioral economics, several studies are laid out and evaluated. The results generally provide a quantitative confirmation of the story of a rise of behavioral economics that can be found in the literature, and add some notable additional insights.